2022
DOI: 10.1177/10781552211072877
|View full text |Cite
|
Sign up to set email alerts
|

Canadian monitoring program of the surface contamination with 11 antineoplastic drugs in 122 centers

Abstract: Introduction Occupational exposure to antineoplastic drugs can lead to long-term adverse effects on workers’ health. Environmental monitoring is conducted once a year, as part of a Canadian monitoring program. The objective was to describe contamination with 11 antineoplastic drugs measured on surfaces. Methods Six standardized sites in oncology pharmacy and six in outpatient clinic were sampled in each hospital. Samples were analyzed by ultra-performance liquid chromatography coupled with tandem mass spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…Between 2012 and 2022, Bussières et al performed a long monitoring programme concerning surface contamination with ICADs (from 3 to 11), mainly cyclophosphamide, ifosfamide and methotrexate at six different locations in numerous Canadian hospitals (from 25 to 122 centres). These different studies revealed a large percentage of positive samples 16 23…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2012 and 2022, Bussières et al performed a long monitoring programme concerning surface contamination with ICADs (from 3 to 11), mainly cyclophosphamide, ifosfamide and methotrexate at six different locations in numerous Canadian hospitals (from 25 to 122 centres). These different studies revealed a large percentage of positive samples 16 23…”
Section: Introductionmentioning
confidence: 99%
“…Different ICADs usually used in hospitals were included as hazardous drugs. Several studies evaluating the occupational exposure to ICADs have been performed in a single compounding unit for shorter or longer periods of a few months including or not including care units 11 14–16. Others were carried out in different hospitals either in different care units or in compounding units 9 11 17–21.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that the floor inside the biological safety cabinet is one of the most contaminated sites. 6,35 As an example, healthcare workers can be in contact with ADs when they manually remove overshoes that have been in contact with the contaminated floor in the CU; it can be a source of spreading ADs in other areas. Not all the respondents in CU were aware that the surface of a vial of ADs can be a source of contamination, as shown by several studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Acute and longterm toxicity can occur, such as genotoxic damage or adverse reproductive outcomes. 2,3 ADs are found at every stage of the hospital medication system 4 and on many surfaces in the pharmacy and in the outpatient clinic 5,6 but also on the workers' hands. 7 Traces of ADs are still found despite the implementation of decontamination measures.…”
Section: Introductionmentioning
confidence: 99%
“…Regular monitoring of environmental contamination has been carried out for several years in German ( 23 ), Italian ( 24 ), Czechoslovakian ( 19 ), Canadian ( 20 ) or American hospitals ( 21 ). These monitoring have shown that the risk of healthcare exposure is not systematically related to the level of environmental contamination or to the activity of the chemotherapy process but more to the practices and awareness of healthcare workers.…”
Section: State Of Artmentioning
confidence: 99%